(3OYhi GdWdGb ef GdRhL hGfcGQ GdRhLI dgs - (3Gdbej, GdejQRG Gdbej, Gdbej, CHh GdbGSe Hf eMeO MSjf Gdbej, J (B1231(3g` (B1816(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg hcai hGdUdhI Ydi fHjg hYdi YHGOg GdPjf GUWai, agPg cdeGJ aj HjGf eSFdI hbY GdJTGLQ ajgG Hjf Cgd YUQfG hgh Cf GdQLd EPG bGd WdbJ RhLJj hCfcQJ GdRhLI WdGbgG agd jSeY CbQGQ GdQLds
(3BNQgG (B:s
(3BNQgG(B: (3bGd bGFd GdWdGb Cf jbhd dgG GYJOj Ch jbhd dgG CfJ WGdb Edi ZjQ Pdc ef GdCLfGS hGdXGgQ ef Jdc GdCLfGS Cf PGc cGa aj KHhJ GdWdGb hdG jWGdH efg GdEKHGJ hGdLhGH dG JfcQ KHhJg eY JUOjbgG Ch LgGdJgG hCeG dh cPHJ hCfcQJ adG OdGdI aj GdQhGjGJ hcdeGJ GdabgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 183s
(3GdPQjYI, L (B8: 145s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis